Aging increases the expression of vasopressin receptors in both the kidney and urinary bladder. Issue 1 (12th October 2018) - Birder, Lori A.; Wolf‐Johnston, Amanda S.; Jackson, Edwin K.; Wein, Alan J.; Dmochowski, Roger
Abstract : Aims: The goal of this study was to determine whether aging effects the expression of V 1a and V 2 vasopressin receptors in the urinary bladder mucosa (UBM) and kidney. Methods: UBM and kidneys were obtained from young (3 months‐of‐age) and old (25‐30 months‐of‐age) female Fisher 344 rats. Tissue samples were analyzed by western blotting for V1a and V2 receptor expression, and rat plasma levels of vasopressin levels were measured by ELISA. Results: V 1a and V 2 receptors were detected in both the UBM and kidneys. Aging significantly ( P < 0.05) increased the expression of V 2 receptors by 2.80 ± 0.52 and 6.52 ± 1.24‐fold in the UBM and kidneys, respectively. Aging also increased V 1a receptor expression in the kidneys (5.52 ± 1.05 fold; P < 0.05), but not in the UBM. To the best of our knowledge, because this is the first detection of V 2 receptors in the mammalian bladder mucosa, we also probed human UBM for V 2 receptors and observed high expression in human UBM. Unlike V 1a and V 2 receptors, aging had only a minor effect on plasma vasopressin levels (8% increase). Conclusions: V 2 receptors are substantially increased in the aging UBM. The role of these receptors in UBM is as yet undefined, but given their presence and action in the kidneys, the possible effect of these receptors in free water regulation should be considered. The large age‐related increase in the expression of V 2 receptors in both the UBM and kidney may contribute to the effectiveness of desmopressin in age‐related nocturia.